Progressive retinal atrophy in turkish shepherd dog; a case report - Mustafa Arican; Elgin Orcum Uzunlu; Yasemin Tanirli; Halil Caltiner; Iremsu Satici (Eurasian Journal of Veterinary Sciences)
Progressive retinal atrophy (PRA) is described as an inherited degenerative disease of the retina that is common in dogs. The case was a 9-year-old female Turkish shepherd dog. It was presented to the Small Animal Hospital with complaints of polyuria and stranguria. After examination, the diagnosis was acute hepatitis. Medical treatment (ursofalk, milk thistle, prednisolone and N acetyl cystein) was given. The case lost vision after three days of treatment. The ophthalmological examinations were performed as included slit lamp, Schirmer's tear test, applanation tonometry, fluorescein staining and ultrasound. Ophthalmoscopic and fundoscopic examinations revealed hyperreflectivity and colour change in the tapetal region, marked attenuation of retinal vessels, depigmentation in the non-tapetal region, and optic disc atrophy with scalloped borders. Fundoscopic examination revealed retinal degeneration in both eyes. The aim of this case report is to diagnose PRA in Turkish shepherd dogs, to highlight its significance and to share the results with clinicians.